Anaemia among Adolescents in a Coastal District of India - Ayushi Agrawal; Avinash Shetty; George P Jacob; Asha Kamath (Medsci Publications, 2018)
Introduction: Globally, anaemia affects 1.62 billion people, corre- sponding to 24.8% of the population and South Asia contributes the highest proportion. As awareness about anaemia and its im- plication on the health has increased, nations and organizations worldwide are taking steps to combat the problem. This study   was formulated with the objective to assess the prevalence of anaemia and the socio demographic, dietary factors associated with anaemia among adolescent boys and girls in a better per- forming coastal district of India. Methodology: A cross sectional study was conducted in the rural field practice area enrolling 526 adolescent. A pretested, validated semi-structured questionnaire was used. Hemoglobin estimation was done using Hemo cue analyser. Result: The total prevalence of anaemia among boys and girls was 30.7% and 45.7% respectively (p<0.001). The prevalence of anae- mia was found to decrease with increasing age among boys whereas it was found to be increasing among girls. Other demo- graphic factors like education and occupation of parents, religion, socio-economic status and dietary pattern had no statistical sig- nificance. Conclusion: The problem of anaemia is high among males though comparatively lower than females. Other causes of anaemia need to be identified to overcome the problem of anaemia.